PEMAKAIAN BAHASA DALAM KOMUNITAS BACKPACKER INDONESIA: KAJIAN SOSIOLINGUISTIK - , FRANCISCA CHRISTY ROSANA, Drs. Tri Mastoyo Jati Kesuma, M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Nowadays, backpacker is a new lifestyle that attracts many people, especially the young ones. As the people who do backpacking in Indonesia rise in the recent time, the backpacker communities ae created. As the time goes, the backpacker communities have shown their existence more and more. Their existence can be seen in various kinds of articles, both in printed and online media. In many some books of backpackerâs stories there are many special term written in. It occurs due to the usage of the terms. Most of the terms used by backpackers are foreign language, especially in English. They do not use that terms correctly. The using of language in backpackerâs communities has its own unique and there are some special terms in it A study of language use in backpacker communities implemented in three stages, collecting, analyzing, and presenting. Data taken from BWISK, National Geographic Traveller Indonesia, and www.backpackerindonesia.com. Data were taken from that magazine and website because the author assume that the source is the most representative source. The position of register in backpacker communities in the society has met the concepts of many aspects in trip now, unlike before when it could not be described of expressed. Terms in backpackerâs communities have also met the characteristics as register.they have their own unique compared to the other terms known by people in general and have become a way in intragroup communication. Furthermore, the author will also discuss the usage of terms in foreign language, especially in English, code-mixing, and social functions contained in them. Code-mixing occurs from the differetiation of cultural background, language, and education between backpackerâs communities in Indonesia and the origin backpacker communities. Code-mixing also occurs from the limitation of language in expressing something and there is no equivalent concept that meet the wanted meaning. Code-mixing divided in two parts, inner code, and outer code. Terms uptake and code-mixing have affected the function of register backpackerâs communities language function. The language function affected by social factors and becomes social function.